Heterogenous expression of endocrine and progenitor cells within the neonatal porcine pancreatic lobes–Implications for neonatal porcine islet xenotransplantation. (7th February 2023) - Seeberger, Karen L; Salama, Bassem F; Kelly, Sandra; Rosko, Mandy; Castro, Chelsea; DesAulniers, Jessica; Korbutt, Gregory S
Abstract: Neonatal porcine islets (NPIs) are a source of islets for xenotransplantation. In the pig, the pancreatic lobes remain separate, thus, when optimizing NPI isolation, the pancreatic lobes included in the pancreatic digest should be specified. These lobes are the duodenal (DL), splenic (SL) and connecting (CL) lobe that correspond to the head, body‐tail, and uncinate process of the human pancreas. In this study we are the first to evaluate all three neonatal porcine pancreatic lobes and NPIs isolated from these lobes. We report, a significant difference in endocrine and progenitor cell composition between lobes, and observed pancreatic duct glands (PDG) within the mesenchyme surrounding exocrine ducts in the DL and CL. Following in vitro differentiation, NPIs isolated from each lobe differed significantly in the percent increase of endocrine cells and final cell composition. Compared to other recipients, diabetic immunodeficient mice transplanted with NPIs isolated from the SL demonstrated euglycemic control as early as 4 weeks ( p < 0.05) and achieved normoglycemia by 6 weeks post‐transplant ( p < 0.01). For the first time we report significant differences between the neonatal porcine pancreatic lobes and demonstrate that NPIs from these lobes differ in xenograft function.